2015
DOI: 10.1186/s13104-015-1339-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with primary open angle glaucoma and normal tension glaucoma at a university hospital: a cross-sectional retrospective study

Abstract: BackgroundThe characteristics of glaucoma patients and their response to therapy may differ by institution, region and country. Therefore, clinicians should understand the distinctiveness of their patients. Here, we profile primary open angle glaucoma (POAG) and normal tension glaucoma (NTG) patients at a major university hospital in Japan.MethodsThis study included 523 eyes from 523 POAG and NTG patients who underwent full clinical ophthalmologic evaluations at Tohoku University Hospital. Clinical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
(18 reference statements)
1
17
0
2
Order By: Relevance
“…Glaucoma is an optic neuropathy characterized by the progressive death of retinal ganglion cell (RGC) axons and the irreversible loss of vision 6 . Although elevated intraocular pressure (IOP) is the most important risk factor for glaucoma, in some patients progress continues despite normal IOP, suggesting that IOP-independent factors also influence glaucoma progression 7 , 8 . Furthermore, many previous reports have indicated that oxidative stress-associated compounds increase in the eyes and bodily fluids of human glaucoma patients 9 12 , in particular oxidized DNA 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is an optic neuropathy characterized by the progressive death of retinal ganglion cell (RGC) axons and the irreversible loss of vision 6 . Although elevated intraocular pressure (IOP) is the most important risk factor for glaucoma, in some patients progress continues despite normal IOP, suggesting that IOP-independent factors also influence glaucoma progression 7 , 8 . Furthermore, many previous reports have indicated that oxidative stress-associated compounds increase in the eyes and bodily fluids of human glaucoma patients 9 12 , in particular oxidized DNA 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A study at Tohoku University Hospital found that the mean age of POAG patients was 63.4 ± 12.4 years. 13 It is known that the factor of increasing age has more opportunities to make people suffer from POAG. It is known that POAG is a disease with chronic and progressive optic nerve damage which has slow progressivity and asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure is determined by the velocity of the formation of aqueous humor by the ciliary body and the obstacles that occur in trabecular meshwork. 14 The results of a study conducted by Yokoyama, et al (2015) at Tohoku University Hospital received a range of intraocular pressure values of 11-20 mmHg. 13 In this study, the highest intraocular pressure results of POAG patients were found in the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important risk factors is elevated intraocular pressure (IOP), which promotes mechanical stress in RGCs and leads to the development of glaucoma. However, many patients, especially in Asia, experience a continued progression of visual eld defects despite normal IOP, suggesting that IOPindependent factors also in uence glaucoma progression [2]; thus, glaucoma is a multifactorial disease.…”
Section: Read Full License Introductionmentioning
confidence: 99%